Are plasma drug concentrations still necessary? Rethinking the pharmacokinetic link in dose–response relationships - Simon, Nicolas; von Fabeck, Katharina (Frontiers in Pharmacology, 2025)
Plasma drug concentrations have historically played a central role in pharmacology, serving as a measurable intermediary between administered dose and clinical response. This model, linking Dose, Concentration and Effect, underpins therapeutic drug monitoring, pharmacokinetic/pharmacodynamic (PK/PD) modeling, and regulatory evaluation. Yet, numerous examples challenge the assumption that plasma concentrations are necessary or sufficient to predict drug effects. Drugs acting locally, exhibiting delayed pharmacodynamics, or relying on active metabolites often dissociate systemic levels from clinical efficacy. Furthermore, modern tools such as receptor occupancy imaging, functional biomarkers, and systems pharmacology offer richer representations of drug action. Drawing on Judea Pearl’s framework for causal inference, we question whether plasma concentrations lie on the true causal pathway between dose and effect, or whether they sometimes obscure rather than reveal pharmacological mechanisms. Using clinical examples and conceptual analysis, we argue for a more selective targeted and context-sensitive use of plasma concentrations. This approach values their usefulness while cautioning against overuse. A structured decision framework is proposed to help determine when plasma monitoring is informative, and when alternative approaches may be more appropriate.